2019
DOI: 10.1021/acs.jpcc.9b03873
|View full text |Cite
|
Sign up to set email alerts
|

Surface Film Formation and Dissolution in Si/C Anodes of Li-Ion Batteries: A Glow Discharge Optical Emission Spectroscopy Depth Profiling Study

Abstract: Addition of a certain amount of Si to state of the art graphite anodes has become the most prominent option to increase the energy density of Li-ion cells. However, the distribution of Si in the depth of Si/C anodes is difficult to measure with established methods. In this paper, we present a semiquantitative depth profiling method based on glow discharge optical emission spectroscopy (GD-OES). The calibration of this method covers 0−100 wt % Si content in the anode and is validated by pilot-line-coated Si/C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 41 publications
3
32
0
1
Order By: Relevance
“…A lower maximum and a broader distribution was observed for the Si distribution of the aged cell, which indicated that the formed film extended more into the depth of the anode compared with the anode from the fresh cell. These results for the cell cycled at 25 °C were consistent with depth profiling results for the same cell type cycled at 0 °C and 45 °C reported previously . The most likely formed Li silicates consume cyclable Li, which was consistent with the decelerated capacity fade curve in Figure .…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…A lower maximum and a broader distribution was observed for the Si distribution of the aged cell, which indicated that the formed film extended more into the depth of the anode compared with the anode from the fresh cell. These results for the cell cycled at 25 °C were consistent with depth profiling results for the same cell type cycled at 0 °C and 45 °C reported previously . The most likely formed Li silicates consume cyclable Li, which was consistent with the decelerated capacity fade curve in Figure .…”
Section: Resultssupporting
confidence: 91%
“…These results for the cell cycled at 25 °C were consistent with depth profiling results for the same cell type cycled at 0 °C and 45 °C reported previously . The most likely formed Li silicates consume cyclable Li, which was consistent with the decelerated capacity fade curve in Figure . The loss of cyclable Li has also been observed for other cells without Si compound in the anode .…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations